2012
DOI: 10.1161/strokeaha.112.656710
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cortical Hemodynamics by Multichannel Near-Infrared Spectroscopy in Steno-Occlusive Disease of the Middle Cerebral Artery

Abstract: Background and Purpose-In a pilot study we evaluated near-infrared spectroscopy as to its potential benefit in monitoring patients with steno-occlusive disease of a major cerebral artery for alterations in cortical hemodynamics. Methods-Cortical maps of time-to-peak (TTP) in 10 patients unilaterally affected by severe stenosis or occlusion of the middle cerebral artery were acquired by multichannel near-infrared spectroscopy after bolus application of indocyanine green. Hemodynamic manifestations were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…ICG [82]. Quality of the signals measured suggest that the instru− ment can be used in estimation of brain perfusion using techniques proposed in several previous studies [37,39,40,44,83,84].…”
Section: Discussionmentioning
confidence: 98%
“…ICG [82]. Quality of the signals measured suggest that the instru− ment can be used in estimation of brain perfusion using techniques proposed in several previous studies [37,39,40,44,83,84].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in the present study, BFI was the parameter that showed the best correlation with rCBF. Its usefulness has been reported in patients with acute ischemic stroke and congenital heart disease, as well as in cerebral blood flow monitoring during carotid endarterectomy 2 , 5 8 . It has been previously reported that TTP, RT, and BFI significantly change in patients with cerebral infarction, and that the TTP measures obtained from NIRS/ICG test strongly correlated with those obtained by MR perfusion imaging 6 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…19 Multichannel NIRS has also been applied for perfusion measurement in adults with MCA stenosis and a delayed perfusion predominantly in the vascular border zone has been found in Ref. 20. Although the anterior cortical border zone is a well described area for (hemodynamic) infarction in carotid artery disease, 21 no experimental studies examining cerebral autoregulation in this area exist in humans so far because of possible harm during pharmacological blood pressure reduction.…”
Section: Discussionmentioning
confidence: 99%